PENGAWASAN IMPELEMENTASI â€œGREEN ACCOUNTINGâ€ BERBASIS UNIVERSITY SOCIAL RESPONSIBILITIES (USR) DI UNIVERSITAS NEGERI SEMARANG SERTA STUDI KOMPARASI UNIVERSITAS SE-KOTA SEMARANG - Sari, Maylia Pramono; Hadiprajitno, Paulus Basuki (JURNAL AKUNTANSI DAN AUDITING, 2013)
Implementing Green Accounting based on the Corporate Social Responsibility (CSR) begins tobe rapidly implemented in Indonesia. The shift of paradigm and company’s orientation to paymore attention to all stakeholders gives impacts on the company’s social role and responsibilitieswhich is commonly called as the Corporate Social Responsibilities (CSR). In higher education,the University’s responsibilities for society is called University Social Responsibility(USR), is basically an ethical policy which influences the quality of university’s communityperformance that consists of students, officers, lecturers and all the university’s staffs throughthe management that responsible toward education, cognitive, employment and environmentwhich are produced by university through some interactive dialogue with society aiming forproducing and developing sustainable human resources. So is Semarang State University as aconservation university which implements University Social Responsibility (USR) to achieve theGood University Governance (GUG). Based on the above statement of problems, this researchaims to gain proofs and investigate, measure and examine the performance of Semarang StateUniversity’s management board whether or not they have conducted the USR well. Beside that,this research also aims to compare the performance and social responsibility between SemarangState University as a Conservation University and other University in Semarang. Has SemarangState University as a conservation university which indeed possesses more conservation valuescompare to the other universities been able to successfully carry out its social responsibilitybetter? In this research, the population used were all universities located in Semarang. In testingthe hypothesis the research used the Independent Sample T Test as confirmation, that is as atesting tool which is used to analyze the comparison by using T Test for two samples whichmatched because the data distributed normally. It aims to find out whether both group have thesame average or significantly different. The research result shows that simultaneously there is nosignificant difference in terms of performance and and social responsibility between SemarangState University as a conservation university compare to the other universities in Semarang.Partially, from four variables used to conduct the test, there is only one variable, that is theEnvironmental Involvement which is statistically has a significant dofference between SemarangState University to the other universities in Semarnag. Meanwhile the other three variables, theyare Environmental Awareness, Environmental Reporting and Environmental Audit, do not showany significant difference. Suggestion for Semarang State University as a conservation universityis to improve the performance and responsibility especially in terms of Environmental Reportingand Environmental Audit.